Inheritance of cotyledon storage proteins in European sweet chestnut (Castanea sativa Miller) - Martín, M.A.; Alvarez, J.B.; Gutierrez, J.C.; Martin, L.M. (Forest Systems, 2012)
A first approximation to the inheritance of cotyledon storage proteins was studied in European sweet chestnut (Castanea sativa Mill.) by evaluating the offspring of a controlled cross between two local chestnut varieties (Corriente and Pilonga) from southern Spain. The analysis was carried out in 15 polymorphic bands corresponding to the albumin fraction of the storage proteins. The relationship between bands displayed one case of allelism and four of linkage. These results should be considered as the baseline of the genetics of these proteins and suggest that they could be useful for the evaluation of the genetic variability in chestnut.